STAGES OF THE INVESTMENT PROJECT MANAGEMENT PROCESS AND INVESTMENT ATTRACTIVENESS ASSESSMENT MECHANISMS (Scientific journal of the Fergana State University, 2026)
The article analyzes the essence of investment projects and the factors influencing their implementation in the context of deepening structural transformations of Uzbekistan’s economy. A step-by-step approach to selecting the most efficient forms of capital investment has also been developed.